Operative Time Longer Than 240 Minutes is Predictive of 30-Day Complications After Vaginal Hysterectomy [43]. (May 2015) - Catanzarite, Tatiana L.; Vieira, Brittany; Shih, Kevin; Kim, John Y.; Milad, Magdy Peter
Abstract : INTRODUCTION: The relationship between operative time and morbidity is incompletely understood in gynecology. We aimed to evaluate the effect of operative time on 30-day complication rates after vaginal hysterectomy. METHODS: Patients undergoing vaginal hysterectomy for benign indications from 2005 to 2012 were identified in the American College of Surgeons National Surgical Quality Improvement Program database. Clinical characteristics and complications were compared for patients with operative time shorter and longer than 240 minutes. Multivariable analysis was performed to determine the independent effect of operative time on complications. RESULTS: A total of 10, 311 vaginal hysterectomies were identified. Complications increased significantly as surgical duration increased, with an inflection point at 240 minutes. Characteristics associated with operative time longer than 240 minutes included older age, nonsmoking status, hypertension, chronic obstructive pulmonary disease, higher ASA (American Society of Anesthesiologists) level, higher relative value units average, inpatient status, general anesthesia, and resident physician involvement. Operative time longer than 240 minutes was associated with increased rates of overall complications (15.7% compared with 6.7%, P <.001), medical complications (13.5% compared with 5.6%, P <.001), urinary tract infection (UTI; 8.9% compared with 3.5%, P <.001), blood transfusion (4.3% compared with 1.5%, P <.001), and reoperation (2.9% compared with 1.2%, P =.02), although mortality rates were similar (0% compared with 0.4%, P =.74). After multivariable analysis, longer operative time independently predicted overall complications, medical complications, UTI, and reoperation. CONCLUSION: We demonstrated that operative time longer than 4 hours during vaginal hysterectomy is predictive of 30-day overall complications, medical complications, UTI, and reoperation. Future research should aim to identify modifiable contributors to prolonged operative time.